Complications after Septoplasty - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
Deviation of the nasal septum (code J34.2 according to ICD 10) is a natural or acquired permanent displacement of the bony or cartilaginous structures, the nasal septum, accompanied by nasal breathing disorders ("Otorhinolaryngology" VTPalchun, Moscow, 2007). The nasal septum consists of cartilage and bony structures that divide the nasal cavity into two relatively equal halves and shape the direction of the airflow inside the nose. Thanks to this, the normal formation of free nasal breathing occurs, the breathing air is warmed and moistened, other protective functions of the nose work normally, and the sense of smell is formed. Curvature can either occur as a result of direct trauma to the nose, or it can develop gradually as a person grows, most people see significant curvatures in early childhood nasal injuries. - fall, birth injuries, but it seems unlikely to prove it; This is due to the long development time.